Analysis on Characteristics of Late Rice Evapotranspiration Based on a New Ultrasonic Paddy Field Evapotranspiration Instrument - Mei DENG; Wanhua HUANG; Tianying WANG; Jing LI (Guangdong nongye kexue, 2022)
【Objective】The diurnal variation, daily average evapotranspiration and cumulative evapotranspiration of late rice were analyzed. Based on the characteristics of evapotranspiration under typical weather conditions, the practical applicability of the new paddy evapotranspiration instrument was discussed.【Method】With the double-cropping late rice as research object, based on the water balance method, the evapotranspiration of late rice in 2017-2019 was measured by using a new type of ultrasonic evapotranspiration instrument.【Result】The actual data collection rate and effective data acquisition rate of the new ultrasonic evapotranspiration instrument are above 93%, and the measurement accuracy can reach 0.2 mm, which can ensure the availability of field observation data in terms of data stability. Based on the analysis of the evapotranspiration of double-cropping late rice on different time scales, it is found that the evapotranspiration of late rice in the whole growth period is about 466 mm, among which the accumulated evapotranspiration in the tillering stage is the highest, about 135 mm, and the average evapotranspiration in the jointing-heading stage of late rice is the highest, which is 5.4 mm/d, indicating that late rice requires the most water at the tillering and jointing-heading stages. Under typical weather conditions (except rainy days), the diurnal variation of late rice evapotranspiration is in a "Ω" type, and the peak value of the evapotranspiration curve on sunny days is the largest, which is 1.3 mm/h. According to the fitted R2 and p values, the evapotranspiration on sunny day, partly cloudy day and cloudy day conditions is distributed as a sixth-order curve.【Conclusion】The research on the eigenvalues of rice evapotranspiration measured by the new type of evapotranspiration instrument and its applicability can provide an important reference for promoting the use of low-cost, high-precision and convenient new type of rice field evapotranspiration measuring instrument.